2012
DOI: 10.1001/archpediatrics.2011.183
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Decreases in Risk Exposure and Youth Problem Behaviors After Installation of the Communities That Care Prevention System in a Randomized Trial

Abstract: To test whether the Communities That Care (CTC) prevention system reduced levels of risk and adolescent problem behaviors community-wide 6 years after installation of CTC and 1 year after study-provided resources ended.Design: A community randomized trial.Setting: Twenty-four small towns in 7 states, matched within state, randomly assigned to control or intervention condition in 2003.Participants: A panel of 4407 fifth-grade students was surveyed annually through 10th grade from 2004 to 2009.Intervention: A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 52 publications
1
125
0
5
Order By: Relevance
“…Such partnerships have been the focus of community-based prevention trials in the USA, such as the CTC or the Promoting School Community University Partnerships to Enhance Resilience prevention models. 52,110 In the CTC model, broad-based community coalitions that include representatives of government, non-governmental organisations, service sectors, and key community leaders receive structured training workshops and proactive technical assistance for assessing their prevention needs, targeting these needs with tested and efficacious prevention strategies, and ensuring that these new strategies are well implemented and integrated with existing prevention efforts. 111 A randomised, controlled assessment has shown that CTC substantially increased the number and scope of prevention services in intervention compared with control communities, and produced community-wide reductions in alcohol and tobacco use and delinquent behaviour that were sustained 2 years later.…”
Section: Building Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Such partnerships have been the focus of community-based prevention trials in the USA, such as the CTC or the Promoting School Community University Partnerships to Enhance Resilience prevention models. 52,110 In the CTC model, broad-based community coalitions that include representatives of government, non-governmental organisations, service sectors, and key community leaders receive structured training workshops and proactive technical assistance for assessing their prevention needs, targeting these needs with tested and efficacious prevention strategies, and ensuring that these new strategies are well implemented and integrated with existing prevention efforts. 111 A randomised, controlled assessment has shown that CTC substantially increased the number and scope of prevention services in intervention compared with control communities, and produced community-wide reductions in alcohol and tobacco use and delinquent behaviour that were sustained 2 years later.…”
Section: Building Capacitymentioning
confidence: 99%
“…111 A randomised, controlled assessment has shown that CTC substantially increased the number and scope of prevention services in intervention compared with control communities, and produced community-wide reductions in alcohol and tobacco use and delinquent behaviour that were sustained 2 years later. 76,110 As efficacious programmes become more widely adopted across communities and nations, the need for strategies to enhance long-term sustainability are crucial. Research on the conditions that facilitate or undermine the maintenance of new initiatives is beginning to emerge.…”
Section: Building Capacitymentioning
confidence: 99%
“…This resulted in the identification of a further six articles that appeared to meet the inclusion criteria (Hawkins et al, 2012;Brown et al, 2007;Fagan et al, 2009;Wagenaar et al, 2000aWagenaar et al, , 2000bWest et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…These included school-based programs, family-focused programs, and community-based, youth-focused programs (such as support, tutoring and mentoring programs). Evaluation data from a panel of students who were in Grade 5 at baseline (2004) and surveyed annually until 2007 found significant differences between intervention and control communities for past 30-day drinking (AOR 0.70 for nondrinkers at baseline; 0.85 for drinkers at baseline) and binge drinking (AOR 0.77 for non-drinkers at baseline; 0.90 for drinkers at baseline) (Oesterle et al, 2010); and the lower incidence of alcohol consumption, tobacco smoking and delinquent behavior was still evident in the 2009 survey, 12 months after the studyprovided resources ended (Hawkins et al, 2012). Interviews with community leaders (928 participants, four waves) found no absolute difference between intervention and control communities in 2009 community norms against adolescent drug use, but a greater increase in this support from baseline; and no difference in general community support for prevention, community collaboration (Rhew et al, 2013).…”
Section: Targeting Whole-of-communitymentioning
confidence: 99%
“…Results. Hawkins et al (2009Hawkins et al ( , 2012 evaluated the effectiveness of CTC in an ambitious large-scale randomized experiment (the Community Youth Development Study). Twenty-four communities across the United States (in seven states) were placed into 12 matched pairs, and one community in each pair was chosen at random to receive CTC.…”
Section: B Communities That Carementioning
confidence: 99%